2014
DOI: 10.1891/0886-6708.vv-d-13-00018
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Increased Risk for Lethal Violence in Intimate Partner Relationships Among Ethnically Diverse Black Women

Abstract: The purpose of this study was to identify factors associated with increased risk for lethal violence among ethnically diverse Black women in Baltimore, Maryland (MD) and the US Virgin Islands (USVI). Women with abuse experiences (n=456) were recruited from primary care, prenatal or family planning clinics in Baltimore, MD and St. Thomas and St. Croix, USVI. Logistic regression was used to examine factors associated with the risk for lethal violence among abused women. Factors independently related to increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 55 publications
0
12
0
5
Order By: Relevance
“…25 Utilization of legal resources could also be an indication of women being at high risk for lethal violence. 26 In our sample, women with multiple types of IPV experiences were, on average, found to be at high risk for lethal violence victimization by their intimate partner based on their scores on the danger assessment, a lethality risk assessment measure for women in abusive relationships. 20 Further, in our study, a substantial proportion of Black women exposed to multiple types of IPV reported depression and PTSD, as found in research conducted on ethnically diverse sample of women exposed to multiple types of victimization.…”
Section: Discussionmentioning
confidence: 97%
“…25 Utilization of legal resources could also be an indication of women being at high risk for lethal violence. 26 In our sample, women with multiple types of IPV experiences were, on average, found to be at high risk for lethal violence victimization by their intimate partner based on their scores on the danger assessment, a lethality risk assessment measure for women in abusive relationships. 20 Further, in our study, a substantial proportion of Black women exposed to multiple types of IPV reported depression and PTSD, as found in research conducted on ethnically diverse sample of women exposed to multiple types of victimization.…”
Section: Discussionmentioning
confidence: 97%
“…This new group of indicators, in contrast with what occurs with the VPR 2015 form, are assessed by officers that know these cases with higher precision due to the periodically established contact with the victims, which aids with the better weighing of the indicators. All of this brings about results that are well related with both risk and protection aspects, supplying evidence about indicators that allows for assessments which compliment these two aspects, to build more dynamic risk assessment instruments through the use of semi-actuarial evaluations in a police context ( Messing et al, 2013 , Sabri et al, 2014 ). The aggressor's attitude towards the victim, translated into behaviors that allow the observation of whether or not they accept and respect the new legal scenario, is translated into risk or protection indicators of which there was no empirical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…It includes questions such as: ‘How often do you have a drink containing alcohol?’ and ‘How often during the last year have you found that you were not able to stop drinking once you started?’ A systematic review of the psychometric properties of the AUDIT, found great performance rates for the tool, across a variety of settings for the 47 studies analysed (Shrestha et al , 2016 ). Studies have found it to be a reliable and effective tool to detect harmful alcohol consumption behaviours (Pitpitan et al , 2013 ; Sabri et al , 2014 ).…”
Section: Methodsmentioning
confidence: 99%